Expression, purification, crystallization and preliminary X‐ray diffraction analysis of the aspartate transcarbamoylase domain of human CAD. Issue 12 (1st December 2013) - Ruiz‐Ramos, Alba; Lallous, Nada; Grande‐García, Araceli; Ramón‐Maiques, Santiago
<x xml:space="preserve">Abstract</x> Aspartate transcarbamoylase (ATCase) catalyzes the synthesis of N‐carbamoyl‐L‐aspartate from carbamoyl phosphate and aspartate in the second step of the de novo biosynthesis of pyrimidines. In prokaryotes, the first three activities of the pathway, namely carbamoyl phosphate synthetase (CPSase), ATCase and dihydroorotase (DHOase), are encoded as distinct proteins that function independently or in noncovalent association. In animals, CPSase, ATCase and DHOase are part of a 243 kDa multifunctional polypeptide named CAD. Up‐regulation of CAD is essential for normal and tumour cell proliferation. Although the structures of numerous prokaryotic ATCases have been determined, there is no structural information about any eukaryotic ATCase. In fact, the only detailed structural information about CAD is that it self‐assembles into hexamers and trimers through interactions of the ATCase domains. Here, the expression, purification and crystallization of the ATCase domain of human CAD is reported. The recombinant protein, which was expressed in bacteria and purified with good yield, formed homotrimers in solution. Crystallization experiments both in the absence and in the presence of the inhibitor PALA yielded small crystals that diffracted X‐rays to 2.1 Å resolution using synchrotron radiation. The crystals appeared to belong to the hexagonal space group P6322, and Matthews coefficient calculation indicated the presence of one ATCase subunit per asymmetric unit, with a solvent content of 48%. However, analysis of the intensity statistics suggests a special case of the P21 lattice with pseudo‐symmetry and possibly twinning.